Peripheral ossifying fibroma of maxillary gingiva with calcification: A case report - Priyanka Tidke; Manvi C Agarwal; Vineet V Kini; Subhasini Singh; Hetul J Patel; Santosh Kumar; Jill Vasant (Wolters Kluwer Medknow Publications, 2024)
Peripheral ossifying fibroma is presented as an exophytic growth with a smooth surface. It is located mostly on the gingiva, and it is an unusual growth of gingiva that occurs after irritational trauma. It is seen in the later decade of life, with the calcifications in the lesion in advanced stages seen on radiographic images. In the present case, a 50-year-old male reported with a huge gingival growth in the left maxillary posterior gingival region; when radiograph was taken, it showed calcifications. The patient was treated by surgical excision of the growth.